Instilling religious character values in elementary school students through Islamic religious education learning - Ika Kartika; Saepudin Saepudin; Efrita Norman; Wiwi Uswatiyah (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
The Instilling Religious Character Values is one of the efforts to shape individuals who believe in and fear God Almighty. Instilling religious character values as early as possible will be more meaningful for elementary school students. This research focused on the fulfillment of self-development-integrated activities, lesson integrated-religious character values, and culture-integrated religious character values carried out by elementary schools. The problem is that most parents are confused about the best way to do this. Should they take do to prepare their children to face their environment. Calculation of religious character values since elementary school is expected to be one of the child's strongholds in facing change. This study aims to describe the cultivation of religious character values from an early age in the digital 5.0 era which is full of extraordinary challenges. This study uses a qualitative approach to library research (Library Research) taken from various reference books, reports and similar previous research results which are useful for obtaining solutions to the problems and social situations studied. The conclusion is that the teachers communicate teaching and learning through learning-integrated values of religious character and culture-integrated values of religious character carried out by the teacher. Some of the processes of cultivating religious character aims to shape students into intelligent and Islamic generations as a provision for students in the future.